2019
DOI: 10.1017/epi.2019.27
|View full text |Cite
|
Sign up to set email alerts
|

Entitlement, Epistemic Risk, and Scepticism

Abstract: Crispin Wright maintains that the architecture of perceptual justification is such that we can acquire justification for our perceptual beliefs only if we have antecedent justification for ruling out any sceptical alternative. Wright contends that this principle doesn't elicit scepticism, for we are non-evidentially entitled to accept the negation of any sceptical alternative. Sebastiano Moruzzi has challenged Wright's contention by arguing that since our non-evidential entitlements don't remove the epistemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Wright (2004 and's has argued that (RISK) is false. However, Moretti (2020) has shown that Wright's arguments are inconclusive. To conclude this paper, let me show that key applications of (RISK) can be vindicated by probability calculus.…”
Section: A General Problem For Epistemic Entitlementmentioning
confidence: 99%
“…Wright (2004 and's has argued that (RISK) is false. However, Moretti (2020) has shown that Wright's arguments are inconclusive. To conclude this paper, let me show that key applications of (RISK) can be vindicated by probability calculus.…”
Section: A General Problem For Epistemic Entitlementmentioning
confidence: 99%
“…THE LEACHING WORRY REVIVED? Moretti (2021) gives a detailed argument that, notwithstanding Wright's original response, the Leaching Worry can indeed be vindicated by orthodox probabilistic reasoning. In particular he argues that, once the pre-theoretical notion of significant epistemic risk is construed probabilistically and the Entitlement theorist allows that we are at significant epistemic risk in accepting cornerstones, significant epistemic risk must be acknowledged to transfer from acceptance of the cornerstones back to acceptance of the various relevant kinds of quotidian propositions about the external world, others' mental states, and the past that we take ourselves habitually and continually to come to know-and, to stress, that the degree of risk transferred is sufficient to undermine both that knowledge and the idea that we are evidentially justified in accepting such quotidian propositions.…”
mentioning
confidence: 99%